Fuel cell electrode catalyst
By supporting Pt or Pt alloy catalyst metal particles on a carbon support and performing sintering treatment under specific conditions, the problem of degradation of catalyst activity in the existing fuel cell is solved, and high activity and long-term stable catalyst performance is achieved.
Patent Information
- Application Number
- CN202380052607.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-05-23
- Publication Date
- 2025-02-28
AI Technical Summary
The conventional method of reducing the supported particles of fuel cell catalysts in the liquid phase may not necessarily show the desired activity, especially when used as a cathode catalyst, the catalyst activity is significantly reduced.
By supporting catalyst metal particles composed of Pt or Pt alloys on a carbon support, and firing under conditions of oxygen partial pressure of 4.0 Pa or more and 800 Pa or less, 300°C or more and 1100°C or less, the particle size and crystallinity of the catalyst metal particles are adjusted to improve catalyst activity.
A fuel cell catalyst with high catalyst activity and high activity can be maintained for a long time when used as a cathode catalyst, thus solving the problem of decreasing catalyst activity in the prior art.
Smart Images

Figure BDA0005233117750000161 
Figure BDA0005233117750000171
Abstract
Description
Technical Field
[0001] The present invention relates to fuel cell electrode catalysts. Background Art
[0002] Fuel cells are highly anticipated as the next generation of batteries. In particular, solid polymer fuel cells have the advantages of low operating temperature, short start-up time, and small size, and have begun to be put into practical use in areas such as automotive driving power sources.
[0003] A solid polymer fuel cell has a structure in which a cathode (air electrode), a solid polymer electrolyte membrane, and an anode (fuel electrode) are stacked in sequence. In such a solid polymer fuel cell, when oxygen or air is supplied to the cathode and a fuel such as hydrogen is supplied to the anode, oxidation and reduction reactions occur at each electrode to generate electricity.
[0004] In a fuel cell, the electrode contains a fuel cell electrode catalyst for promoting the above-mentioned oxidation and reduction reactions. As the fuel cell electrode catalyst, a catalyst having a structure in which catalyst metal particles are supported on a carbon carrier is widely used. As catalyst metal particles of the fuel cell electrode catalyst, Pt particles and Pt alloy particles are known.
[0005] For example, Patent Document 1 describes a method for producing a Pt-supported catalyst, wherein a Pt precursor compound is reduced in a liquid phase in the presence of carrier particles to reduce and support Pt on the carrier particles. In addition, Patent Document 2 describes a method for producing a fuel cell catalyst by using Pt alloy particles as catalyst metal particles to improve the activity of the cathode of a solid polymer fuel cell, and by supporting Pt and an alloy metal on carrier particles and then sintering the particles.
[0006] Prior Art Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 08-084930
[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-142112 Summary of the invention
[0009] Problems to be solved by the invention
[0010] According to the teaching of Patent Document 1, a fuel cell catalyst produced by a method of reducing Pt on carrier particles in a liquid phase may not necessarily show the desired activity. In particular, when the fuel cell catalyst is used as a cathode catalyst, the catalyst activity may be significantly reduced.
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a fuel cell catalyst having high catalytic activity and exhibiting desired catalytic activity when used as a cathode catalyst.
[0012] Means for solving problems
[0013] The present invention is as follows.
[0014] Technical Solution 1 A fuel cell electrode catalyst is a fuel cell electrode catalyst in which catalyst metal particles composed of Pt or a Pt alloy are supported on a carbon carrier,
[0015] When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (111) plane represented by the following formula is 0.626 to 0.630,
[0016] Pt(111) peak intensity ratio = Pt(111) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity).
[0017] Technical Solution 2: The fuel cell electrode catalyst according to Technical Solution 1,
[0018] When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (200) plane represented by the following formula is 0.240 to 0.243,
[0019] Pt(200) peak intensity ratio = Pt(200) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity).
[0020] Technical Solution 3: The fuel cell electrode catalyst according to Technical Solution 1,
[0021] When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (220) plane represented by the following formula is 0.129 to 0.132,
[0022] Pt (220) peak intensity ratio = Pt (220) peak intensity / (Pt (111) peak intensity + Pt (200) peak intensity + Pt (220) peak intensity).
[0023] <Technical Solution 4> According to the fuel cell electrode catalyst described in any one of Technical Solutions 1 to 3, the particle size of the catalyst metal particles is greater than or equal to 3.0 nm and less than or equal to 5.0 nm.
[0024] [Technical Solution 5] According to the fuel cell electrode catalyst described in any one of Technical Solutions 1 to 3, the carbon carrier is particles of furnace conductive carbon black.
[0025] "Technical Solution 6" According to any one of Technical Solutions 1 to 3, the loading amount of the catalyst metal particles represented by the ratio of the mass of the catalyst metal particles to the total mass of the electrode catalyst is greater than 1.0 mass% and less than 50 mass%.
[0026] "Technical Solution 7" A cathode of a fuel cell has a catalyst layer, and the catalyst layer contains the fuel cell electrode catalyst described in any one of Technical Solutions 1 to 3.
[0027] "Technical Solution 8" A fuel cell electrode assembly comprising the cathode described in Technical Solution 7.
[0028] "Technical Solution 9" A fuel cell comprises the fuel cell electrode assembly described in Technical Solution 8.
[0029] "Technical Solution 10" A method for manufacturing a fuel cell electrode catalyst, comprising:
[0030] contacting the carbon support with a catalyst metal precursor;
[0031] reducing the catalyst metal precursor to support catalyst metal particles on the carbon support to obtain an electrode catalyst precursor; and
[0032] The electrode catalyst precursor is calcined under the conditions of an oxygen partial pressure of 4.0 Pa to 800 Pa and a temperature of 500° C. to 1100° C.
[0033] "Technical Solution 11" According to the method for manufacturing a fuel cell electrode catalyst described in Technical Solution 10, the calcination is carried out under reduced pressure.
[0034] [Technical Solution 12] According to the method for manufacturing a fuel cell electrode catalyst described in Technical Solution 10, the calcination is carried out under the circulation of an inert gas.
[0035] Effects of the Invention
[0036] According to the present invention, there is provided a fuel cell catalyst which has high catalytic activity and does not cause a decrease in activity during operation even when used as a cathode catalyst. DETAILED DESCRIPTION
[0037] 《Fuel Cell Electrode Catalysts》
[0038] The fuel cell catalyst of the present invention is a fuel cell electrode catalyst in which catalyst metal particles composed of Pt or a Pt alloy are supported on a carbon carrier.
[0039] When the electrode catalyst was measured by XRD, the peak intensity ratio of the Pt (111) plane represented by the following formula was 0.626 to 0.630,
[0040] Pt(111) peak intensity ratio = Pt(111) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity).
[0041] The fuel cell catalyst of the present invention can be produced, for example, by the following method:
[0042] The method comprises:
[0043] contacting the carbon support with a catalyst metal precursor;
[0044] reducing the catalyst metal precursor to support the catalyst metal particles on the carbon support to obtain an electrode catalyst precursor; and
[0045] The electrode catalyst precursor is calcined under the conditions of an oxygen partial pressure of 4.0 Pa to 800 Pa and a temperature of 300° C. to 1100° C.
[0046] As mentioned above, the fuel cell electrode catalyst manufactured by the method of reducing Pt on the carrier particles in the liquid phase and then not calcining may not necessarily show the desired activity. In particular, if the electrode catalyst is used as a cathode catalyst, the catalyst activity is significantly reduced during the operation of the fuel cell.
[0047] According to the research of the inventors, it is known that in the catalyst metal particles in the fuel cell electrode catalyst manufactured by the Pt reduction loading method without the calcination step, when Pt is reduced and loaded on the particle carrier, the most stable Pt (111) surface grows preferentially. It is known that if the exposure ratio of the Pt (111) surface is high, the catalyst activity is low. This is also verified in the examples described later.
[0048] Therefore, it is conceivable that the Pt-supported carbon (electrode catalyst precursor) obtained by reducing and supporting Pt on a particle carrier is calcined to grow the Pt particle size and adjust the crystallinity of Pt.
[0049] Here, if a large amount of oxygen remains in the atmosphere during sintering, there is a concern that the carbon support will burn and the catalyst metal particles will coarsen. On the other hand, according to the research of the inventors, if there is too little oxygen in the atmosphere during sintering, the (111) surface of Pt will grow preferentially, which cannot solve the above-mentioned problem.
[0050] In the present invention, Pt-supported carbon (electrode catalyst precursor) obtained by reduction-supporting Pt on a particle carrier is calcined under the condition of an oxygen partial pressure of 4.0 Pa or more and 800 Pa or less. In the fuel cell electrode catalyst obtained by such a production method, the combustion of the carbon carrier is suppressed, and the ratio of the Pt (111) plane of the catalyst metal particles is adjusted within an appropriate range, and as a result, the peak intensity ratio of the Pt (111) plane represented by the following formula when measuring XRD: Pt (111) peak intensity ratio = Pt (111) peak intensity / (Pt (111) peak intensity + Pt (200) peak intensity + Pt (220) peak intensity) can be a fuel cell electrode catalyst of 0.626 to 0.630.
[0051] 〈Carbon Support〉
[0052] The carbon carrier in the fuel cell electrode catalyst of the present invention may be, for example, carbon black, graphite, carbon fiber, activated carbon, amorphous carbon, nanocarbon materials, etc. Nanocarbon materials include carbon nanotubes, graphene, fullerene, and the like.
[0053] As the carbon carrier in the present invention, carbon black can be used in particular. Carbon black can be furnace carbon black, channel carbon black, acetylene carbon black, thermal carbon black, etc. The carbon carrier in the present invention can be in particular particles of furnace conductive carbon black.
[0054] The carbon carrier of the present invention has a specific surface area of 10 m2 measured by the BET method with nitrogen as the adsorbent. 2 / g or more, 20m 2 / g or more, 30m 2 / g or more, 40m 2 / g or more, 50m 2 / g or more, 100m 2 / g or more, 150m 2 / g or above, or 200m 2 / g or above, can be 1700m 2 / g or less, 1600m 2 / g or less, 1500m 2 / g or less, 1400m 2 / g or less, 1200m 2 / g or less, 1000m 2 / g or less, 800m 2 / g or less, 600m 2 / g or less, 500m 2 / g or less, 400m 2 / g or less, 300m 2 / g or less, 250m 2 / g or less, or 200m 2 / g or less.
[0055] The specific surface area of the carbon carrier can be, for example, 10 m 2 / g and above 1700m 2 / g or less, 50m 2 / g and above 1500m 2 / g or less, or 100m 2 / g and above 1400m 2 / g or less.
[0056] The particle size of the carbon carrier, as a number average primary particle size measured by electron microscope observation, can be 5 nm or more, 10 nm or more, 20 nm or more, 30 nm or more, or 50 nm or less, 300 nm or less, 200 nm or less, 100 nm or less, or 50 nm or less.
[0057] The particle size of the carbon carrier can be calculated as the number average of equivalent diameters based on electron microscope images of fuel cell electrode catalysts. In addition, the so-called "equivalent diameter" refers to the diameter of a perfect circle having an outer circumference equal to the outer circumference of the measurement object figure.
[0058] 〈Catalyst Metal Particles〉
[0059] The catalytic metal particles are composed of Pt or a Pt alloy and are supported on a carbon carrier.
[0060] When the catalyst metal particles are composed of a Pt alloy, the Pt alloy may be an alloy containing Pt and one or more metals selected from Ti, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Ga, Zr, Hf, Ru, Ir, Pd, Os, Rh and Sn.
[0061] The Pt alloy may typically be a Pt-Fe alloy, a Pt-Co alloy, or a Pt-Ni alloy.
[0062] The proportion of Pt atoms in the Pt alloy, measured as the percentage of the molar number of Pt atoms to the total molar number of metal atoms in the Pt alloy, can be greater than 50 mol%, greater than 60 mol%, greater than 70 mol%, greater than 75 mol%, greater than 80 mol%, or greater than 85 mol%, and can be less than 99 mol%, less than 95 mol%, less than 90 mol%, less than 85 mol%, less than 80 mol%, or less than 75 mol%.
[0063] The average particle size of the catalyst metal particles may be 1.0 nm or more, 1.5 nm or more, 2.0 nm or more, 2.5 nm or more, or 3.0 nm or more, and may be 10.0 nm or less, 8.0 nm or less, 6.0 nm or less, 5.0 nm or less, 4.5 nm or less, or 4.0 nm or less. The catalyst metal particles having an average particle size of 10.0 nm or less have the advantage of high specific activity. The catalyst metal particles having an average particle size of 1.0 nm or more have the advantage of excellent maintenance of specific activity during long-term operation of the fuel cell.
[0064] The particle diameter of the catalytic metal particles may be, for example, 3.0 nm or more and 5.0 nm or less.
[0065] When the catalyst metal particles are Pt particles, the average particle size of the catalyst metal particles can be calculated by the Scherrer equation based on the line width of the diffraction peak of the (220) plane of Pt in the XRD measurement of the fuel cell electrode catalyst. On the other hand, when the catalyst metal particles are Pt alloys, the average particle size of the catalyst metal particles can be calculated by small-angle X-ray scattering or transmission electron microscopy (TEM).
[0066] As described above, when the fuel cell electrode catalyst of the present invention is subjected to XRD measurement, the peak intensity ratio of the Pt (111) plane represented by the following formula is 0.626 to 0.630.
[0067] Pt(111) peak intensity ratio = Pt(111) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity)
[0068] When the peak intensity ratio of the Pt (111) plane is within the range of 0.626 to 0.630, the catalytic activity of the fuel cell electrode catalyst is high, and even when the electrode catalyst of the present invention is used in a cathode of a fuel cell, the high catalytic activity can be maintained for a long time.
[0069] In addition, when the fuel cell electrode catalyst of the present invention is subjected to XRD measurement, the peak intensity ratio of the Pt (200) plane represented by the following formula may be 0.240 to 0.243.
[0070] Pt(200) peak intensity ratio = Pt(200) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity)
[0071] When the peak intensity ratio of the Pt (200) plane is in the range of 0.240 to 0.243, the catalytic activity of the fuel cell electrode catalyst becomes higher.
[0072] In addition, when the fuel cell electrode catalyst of the present invention is subjected to XRD measurement, the peak intensity ratio of the Pt (220) plane represented by the following formula can be 0.129 to 0.132.
[0073] Pt(220) peak intensity ratio = Pt(220) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity)
[0074] When the peak intensity ratio of the Pt (220) plane is in the range of 0.129 to 0.132, the catalytic activity of the fuel cell electrode catalyst becomes higher.
[0075] In the fuel cell electrode catalyst of the present invention, the catalytic metal particles are supported on the carbon support.
[0076] The loading amount of the catalyst metal particles in the fuel cell electrode catalyst of the present invention, measured as the ratio of the mass of the catalyst metal particles to the total mass of the electrode catalyst, can be 1.0 mass %, 5.0 mass %, 10 mass %, 15 mass %, 20 mass %, or 25 mass %, and can be 70 mass %, 60 mass %, 50 mass %, 45 mass %, 40 mass %, or 35 mass %.
[0077] 〈Optional Ingredients〉
[0078] The fuel cell electrode catalyst of the present invention contains a carbon support and catalyst metal particles, and may also contain any components other than these. The arbitrary components that may be contained in the fuel cell electrode catalyst of the present invention may be, for example, one or more components selected from carbon materials other than the carbon support, Ir particles, Ir·Ru alloy particles, Ir oxides, etc. The carbon material other than the carbon support is a carbon material that does not support catalyst metal particles, and may be selected from, for example, graphite, carbon fiber, carbon black, graphitized carbon black, carbon nanotubes, etc.
[0079] 〈Application of fuel cell electrode catalysts〉
[0080] The fuel cell catalyst of the present invention can be used as an electrode catalyst in the cathode or anode of a fuel cell, and is particularly suitable as an electrode catalyst in the cathode of a fuel cell.
[0081] 《Method for producing fuel cell electrode catalyst》
[0082] The fuel cell electrode catalyst of the present invention can be produced, for example, by the following method:
[0083] The method comprises:
[0084] contacting the carbon support with a catalyst metal precursor;
[0085] reducing the catalyst metal precursor to support the catalyst metal particles on the carbon support to obtain an electrode catalyst precursor; and
[0086] The electrode catalyst precursor is calcined under the conditions of an oxygen partial pressure of 4.0 Pa to 800 Pa and a temperature of 300° C. to 1100° C.
[0087] When the catalytic metal particles are Pt particles, a Pt precursor is used as the catalytic metal precursor, a carbon support and the Pt precursor are brought into contact in an appropriate solvent, and then the Pt precursor is reduced to support the Pt particles on the carbon support, thereby obtaining an electrode catalyst precursor.
[0088] The carbon support to be used can be appropriately selected and used depending on the carbon support in the desired fuel cell electrode catalyst.
[0089] The Pt precursor can be appropriately selected from solvent-soluble Pt compounds. For example, the Pt precursor can be appropriately selected from PtCl2, PtCl4, PtBr2, PtS, Pt(CN)2, PtCl2(NH3)2 (dinitrodiammineplatinum), etc.
[0090] The solvent can be selected from solvents that can dissolve the Pt precursor used. For example, when the Pt precursor is PtCl2, hydrochloric acid can be used, when the Pt precursor is PtBr2, hydrobromic acid aqueous solution can be used, when the Pt precursor is PtCl2(NH3)2, nitric acid aqueous solution can be used, and when the Pt precursor is PtCl4, PtS or Pt(CN)2, water can be used.
[0091] The reduction of the Pt precursor can be performed using an appropriate reducing agent. The reducing agent may be, for example, ethanol, acetic acid, acetaldehyde, sodium borohydride, hydrazine, etc. The reduction may be performed at a temperature of 10° C. to 100° C. for a period of 0.5 hours to 8 hours. When sodium borohydride is used as the reducing agent, the reduction temperature is preferably 10° C. to 50° C., and when ethanol, acetic acid, acetaldehyde or hydrazine is used as the reducing agent, the reduction temperature is preferably 60° C. to 100° C.
[0092] In this way, an electrode catalyst precursor in which Pt particles were supported on a carbon support was obtained.
[0093] On the other hand, when the catalytic metal particles are Pt alloy particles, the electrode catalyst precursor can be obtained by, for example, any of the following methods.
[0094] (1) Method of sequentially reducing supported Pt and alloy metals (Method 1):
[0095] In a suitable solvent, the carbon support is brought into contact with a Pt precursor, the Pt precursor is reduced, and Pt particles are supported on the carbon support to obtain Pt-supported carbon;
[0096] In a suitable solvent, the Pt-supported carbon is brought into contact with an alloy metal precursor, and then the alloy metal precursor is reduced to obtain a Pt-alloy metal-supported carbon having alloy metal particles supported on the Pt-supported carbon; and
[0097] The Pt-alloy metal-supported carbon is heated to alloy Pt with the alloy metal, thereby obtaining an electrode catalyst precursor in which Pt alloy particles are supported on the carbon support.
[0098] (2) Method for simultaneously reducing supported Pt and alloy metal (Method 2):
[0099] After the carbon support is brought into contact with the Pt precursor and the alloy metal precursor in an appropriate solvent, the Pt precursor and the alloy metal precursor are reduced to obtain Pt-alloy metal-supported carbon (electrode catalyst precursor) in which Pt particles and alloy metal particles are supported on the carbon support.
[0100] In this specification, "alloy metal" refers to metal other than Pt in the Pt alloy constituting the catalyst metal particles.
[0101] Hereinafter, Method 1 and Method 2 for producing an electrode catalyst precursor in which the catalytic metal particles are Pt alloy particles will be described in order.
[0102] (1) Method of sequentially loading Pt and alloy metal on a carbon support (Method 1)
[0103] In method 1, a carbon support and a Pt precursor are first brought into contact in an appropriate solvent, and then the Pt precursor is reduced to support Pt particles on the carbon support to obtain Pt-supported carbon. This step can be performed in the same manner as the production of an electrode catalyst precursor when the catalytic metal particles are Pt particles.
[0104] Next, the obtained Pt-supported carbon is brought into contact with an alloy metal precursor in a suitable solvent, and the alloy metal precursor is reduced to obtain Pt-alloy metal-supported carbon having alloy metal particles supported on the Pt-supported carbon, which is used as an electrode catalyst precursor.
[0105] The alloy metal precursor can be appropriately selected and used according to the type of alloy metal in the desired fuel cell electrode catalyst. The alloy metal precursor can be appropriately selected and used from solvent-soluble compounds containing the desired alloy metal. For example, it can be a hydroxide, chloride, sulfide, nitrate, sulfate, acetate, etc. of the desired alloy metal.
[0106] The solvent can be selected from solvents that can dissolve the alloy metal precursor used, and can be water, for example.
[0107] The reduction of the alloy metal precursor can be carried out using a suitable reducing agent or neutralizing agent. The reducing agent may be, for example, sodium borohydride, hydrazine, hydrogen, formic acid, etc. The neutralizing agent may be, for example, sodium metaborate, sodium hydroxide, sodium carbonate, ammonia, etc.
[0108] The reduction using a reducing agent can be performed for 0.5 to 8 hours at a temperature of 10° C. to 100° C. When sodium borohydride is used as the reducing agent, the reduction temperature is preferably 10° C. to 50° C., and when ethanol, acetic acid, acetaldehyde or hydrazine is used as the reducing agent, the reduction temperature is preferably 60° C. to 100° C.
[0109] In the reduction of the alloy metal precursor, when a neutralizing agent is used, it is believed that once the alloy metal is supported on the Pt-supporting carbon in a state with a valence of 1 or more, it is reduced by heating and forms an alloy with Pt. The reduction using the neutralizing agent can be performed at a temperature of 60° C. to 100° C. for a period of 0.5 hour to 8 hours.
[0110] In this way, an electrode catalyst precursor in which alloy metal particles are supported on Pt-supported carbon is obtained.
[0111] (2) Method for Simultaneous Reduction of Supported Pt and Alloy Metal (Method 2)
[0112] In method 2, when the carbon support is brought into contact with the catalyst metal precursor, an electrode catalyst precursor is obtained in the same manner as when the catalyst metal particles are Pt particles except that an alloy metal precursor is used together with the Pt precursor as the catalyst metal precursor.
[0113] Next, the electrode catalyst precursor obtained above is calcined under the conditions of an oxygen partial pressure of 4.0 Pa or more and 800 Pa or less and a temperature of 300° C. or more and 1100° C. or less, thereby obtaining the fuel cell electrode catalyst of the present invention. Through this process, when the catalyst metal particles are Pt particles, the catalyst metal particles are grown while controlling the exposed crystal surface of Pt. In addition, when the catalyst metal particles are Pt alloy particles, Pt and the alloy metal are alloyed, and the catalyst metal particles are grown while controlling the exposed crystal surface of Pt.
[0114] The oxygen partial pressure during firing may be 4.0 Pa or more, 5.0 Pa or more, 10 Pa or more, 20 Pa or more, 50 Pa or more, 100 Pa or more, or 200 Pa or more. In addition, the oxygen partial pressure during firing may be 800 Pa or less, 700 Pa or less, 600 Pa or less, 500 Pa or less, 400 Pa or less, or 300 Pa or less.
[0115] The atmosphere during firing may be under reduced pressure or in the presence of an inert gas.
[0116] From the viewpoint of controlling the oxygen partial pressure in the atmosphere within the above-mentioned predetermined range, the pressure when the atmosphere during sintering is set to a reduced pressure can be 4.0 Pa or more, 5.0 Pa or more, 10 Pa or more, 20 Pa or more, 50 Pa or more, 100 Pa or more, or 200 Pa or less, and can be 900 Pa or less, 800 Pa or less, 700 Pa or less, 600 Pa or less, 500 Pa or less, or 400 Pa or less.
[0117] When the sintering atmosphere is in the presence of an inert gas, the inert gas may be, for example, nitrogen, helium, neon, argon, krypton, etc. Argon is preferred as the inert gas because it contains few impurities (especially oxygen) and is easily available.
[0118] When the calcination atmosphere is set to the presence of an inert gas, the calcination can be performed while the inert gas is flowing, or the calcination can be performed without moving the inert gas relative to the electrode catalyst precursor. From the viewpoint of maintaining the oxygen partial pressure near the electrode catalyst precursor at a desired oxygen partial pressure, it is preferred to perform the calcination while the inert gas is flowing.
[0119] The sintering temperature may be 450°C or higher, 500°C or higher, 550°C or higher, or 600°C or higher, and may be 1100°C or lower, 1000°C or lower, or 900°C or lower.
[0120] The firing time may be 15 minutes or more, 30 minutes or more, 45 minutes or more, 1 hour or more, 1.5 hours or more, or 2 hours or less, and may be 24 hours or less, 12 hours or less, 8 hours or less, 6 hours or less, or 4 hours or less.
[0121] The cathode of a fuel cell
[0122] In another aspect of the present invention, there is provided a cathode of a fuel cell having a catalyst layer comprising the fuel cell electrode catalyst of the present invention.
[0123] The cathode may have a suitable substrate layer and a catalyst layer on the substrate layer, the catalyst layer comprising the fuel cell electrode catalyst of the present invention.
[0124] The substrate layer can be appropriately selected from materials having chemical and mechanical stability to resist fuel cell electrode catalysts and solvents, and heat treatment and pressurization treatment preferably performed during electrode formation. Specifically, for example, sheets of polyimide, polyethylene, polypropylene, polysulfone, polytetrafluoroethylene, etc. can be used.
[0125] The catalyst layer contains the fuel cell electrode catalyst of the present invention, and may contain an ionomer, for example, and may contain any component such as a binder. The ionomer may be, for example, Nafion (sulfonated tetrafluoroethylene (co)polymer).
[0126] 《Fuel cell electrode assembly》
[0127] In another aspect of the present invention, there is provided a fuel cell electrode assembly including the cathode described above.
[0128] The fuel cell electrode assembly may have a structure in which a cathode, a solid polymer electrolyte membrane, and an anode are stacked in this order, and the cathode may be an electrode containing the fuel cell electrode catalyst of the present invention.
[0129] The solid polymer electrolyte membrane and the anode in the fuel cell electrode assembly may be known solid polymer electrolyte membranes and anodes, respectively.
[0130] The fuel cell electrode assembly of the present invention can be produced by a known method except that an electrode containing the fuel cell electrode catalyst of the present invention is used as a cathode.
[0131] Fuel Cell
[0132] In another aspect of the present invention, there is provided a fuel cell comprising the above-mentioned fuel cell electrode assembly. The fuel cell of the present invention may be a solid polymer fuel cell.
[0133] The fuel cell of the present invention includes the fuel cell electrode assembly of the present invention and may have, for example, an air channel or an oxygen channel on the cathode side and a fuel channel on the anode side.
[0134] The fuel cell of the present invention can be produced by a known method except that an electrode containing the fuel cell electrode catalyst of the present invention is used as a cathode.
[0135] Example
[0136] 《Example 1》
[0137] (1) Preparation of electrode catalyst
[0138] 0.7 g of CB1 (furnace conductive carbon black "Vulcan XC72R" manufactured by Cabot Corporation, primary particle size 30 nm, specific surface area 231 m 2 / g) was dispersed in a nitric acid aqueous solution with a concentration of 0.1N to obtain a dispersion. A dinitrodiammineplatinum (II) nitric acid solution was added to the dispersion, and the mixture was stirred for 30 minutes to obtain a mixed solution. Here, the amount of dinitrodiammineplatinum (II) nitric acid solution added was set to an amount in which the ratio of the mass of metal-converted Pt to the total mass of the carbon support and the metal-converted Pt was 30 mass %.
[0139] 8.4 g of ethanol as a reducing agent was added to the stirred mixed solution, and the mixture was heated under reflux for 2 hours to load Pt on the carbon support. The solid content was recovered by filtration, washed with pure water, and dried at 80° C. for 15 hours to obtain a dried product.
[0140] The obtained dried product was calcined at 700° C. for 2 hours in a calcination furnace adjusted to a furnace pressure of 5.0 Pa and a furnace oxygen partial pressure of 5.0 Pa, and then pulverized to obtain an electrode catalyst of Example 1.
[0141] (2) Evaluation of electrode catalyst
[0142] (2-1) Determination of Pt Particle Size
[0143] The XRD results of the obtained electrode catalyst were measured, and the diffraction peak of the (220) plane of Pt was fitted, and the particle size of Pt was calculated using the Scherrer equation from the half-value width.
[0144] XRD measurement was performed under the following conditions.
[0145] Detector: RINT-TTR III, a high-power X-ray diffraction device for horizontal specimens manufactured by Rigaku Corporation
[0146] Tube ball: CuK α (wavelength )
[0147] Output: 50kV-300mA
[0148] Measuring angle range (2θ): 20 to 90°
[0149] Sampling interval: 0.02°
[0150] (2-2) Determination of Pt(111) peak intensity ratio
[0151] In the above XRD measurement, the (111) plane, (200) plane, and (220) plane of Pt were fitted, respectively. The peak intensity ratio of the Pt (111) peak was calculated by the following formula using the peak heights of the fitted peaks.
[0152] Pt(111) peak intensity ratio = Pt(111) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity)
[0153] (3) Evaluation of catalyst activity (specific activity)
[0154] (3-1) Production of a cell for evaluating catalyst activity
[0155] After dispersing the obtained electrode catalyst of Example 1 in water, ethanol was added, and then an aqueous dispersion containing Nafion as an ionomer was added, and ultrasonic dispersion was performed to modulate a cathode (air electrode) catalyst layer forming coating liquid. The obtained cathode catalyst layer forming coating liquid was applied to one side of a Teflon (registered trademark) sheet, and then dried to form a cathode catalyst layer on the sheet.
[0156] Instead of the electrode catalyst of Example 1, a catalyst powder having Pt loaded on Ketjen Black (Ketjen Black International (Co., Ltd.), trade name "EC300") was used. The coating liquid for forming the anode (hydrogen electrode) catalyst layer was prepared in the same manner as the preparation of the coating liquid for forming the cathode catalyst layer, and the anode catalyst layer was formed on the sheet using the coating liquid. The Pt loading in the catalyst powder used in the anode catalyst layer was 30% by mass based on the mass of the catalyst powder.
[0157] On both sides of the polymer electrolyte membrane, the Teflon (registered trademark) sheets having the cathode catalyst layer and the anode catalyst layer obtained above are stacked in a manner such that the catalyst layer forming surfaces face each other, and after transfer by hot pressing, the Teflon (registered trademark) sheets are peeled off to obtain an electrode assembly (MEA) in which the cathode catalyst layer, the polymer electrolyte membrane and the anode catalyst layer are stacked in sequence. Next, a diffusion layer is provided on the surface of each catalyst layer, thereby manufacturing a unit for evaluating catalyst activity.
[0158] (3-2) Evaluation of catalyst activity (specific activity)
[0159] First, the ECSA (electrochemically active area) of the Pt particles was determined using an electrochemical measurement system manufactured by Hokuto Denko (Co., Ltd., model name "HZ-5000"), with nitrogen supplied to the cathode at 2.0 L / min and hydrogen supplied to the anode at 0.5 L / min at a cell temperature of 90°C and a humidity of 90%, at a flow rate of 0.01 to 1.20 A / cm 2Cyclic voltammetry (CV) was performed within the range of 1000 nm to determine the area C value of the hydrogen desorption (desorption) wave. The C value obtained and the Pt unit area weight (m-Pt / m 2 -MEA) to calculate ECSA.
[0160] Next, a fuel cell evaluation system manufactured by Toyo Technica Co., Ltd. was used. Air was supplied to the cathode at 2.0 L / min and hydrogen was supplied to the anode at 0.5 L / min under a cell temperature of 90°C and a humidity of 90%. The current density was 0.01 to 0.20 A / cm 2 The voltage value was measured in the range of . Based on the obtained data, the current density showing a voltage of 0.9 V was taken as the catalyst activity. This value was divided by the ECSA obtained above to calculate the specific activity (A / m 2 -Pt).
[0161] 《Examples 2 to 4 and Comparative Examples 1 to 5》
[0162] Electrode catalysts were prepared and evaluated in the same manner as in Example 1 except that the furnace conditions (oxygen partial pressure and pressure) during calcination were adjusted as shown in Table 1. The evaluation results are shown in Table 1.
[0163] 《Example 5》
[0164] The electrode catalyst was prepared and evaluated in the same manner as in Example 1 except that the calcination was performed under an argon gas flow with an oxygen partial pressure of 50 Pa. The evaluation results are shown in Table 1.
[0165] 《Comparative Example 6》
[0166] The electrode catalyst was prepared and evaluated in the same manner as in Example 1 except that calcination was not performed. The evaluation results are shown in Table 1.
[0167] 《Comparative Example 7》
[0168] The electrode catalyst was prepared and evaluated in the same manner as in Example 1 except that the calcination temperature was 400° C. The evaluation results are shown in Table 1.
[0169] 《Examples 6 and 7 and Comparative Examples 8 and 9》
[0170] As the carbon support, CB2 (Ketjenblack EC600JD manufactured by Lion Specialty Chemicals Co., Ltd.) with a primary particle size of 34 nm and a specific surface area of 1,343 m 2 / g), the ratio of the mass of metal-converted Pt to the total mass of the carbon support and the metal-converted Pt was 42 mass %, and the furnace conditions (oxygen partial pressure and pressure) during calcination were adjusted as described in Table 2. The electrode catalyst was prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0171] 《Examples 8 and 9 and Comparative Examples 10 and 11》
[0172] As the carbon support, CB3 (acetylene black "Li435" manufactured by Denka Corporation) with a primary particle size of 23 nm and a specific surface area of 127 m 2 / g), the ratio of the mass of metal-converted Pt to the total mass of the carbon support and the metal-converted Pt was 18 mass %, and the furnace conditions (oxygen partial pressure and pressure) during calcination were adjusted as described in Table 2. The electrode catalyst was prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0173] [Table 11]
[0174]
[0175] [Table 2]
[0176]
[0177] According to Table 1, it was verified that the electrode catalysts of Examples 1 to 5 in which the peak intensity ratio of the (111) plane of Pt as the catalyst metal particle was 0.626 to 0.630 showed higher catalytic activity (specific activity) than the electrode catalysts of Comparative Examples 3 to 5 in which the peak intensity ratio was less than 0.626 and Comparative Examples 1, 2, 6 and 7 in which the peak intensity ratio was greater than 0.630.
[0178] The electrode catalyst containing catalytic metal particles having a peak intensity ratio of Pt (111) plane of 0.626 to 0.630 is obtained by adjusting the oxygen partial pressure of the surrounding atmosphere to 4.0 Pa or more and 800 Pa or less during calcination after Pt is supported on a carbon carrier.
[0179] In the electrode catalysts of Comparative Example 6 without calcination and Comparative Example 7 with low calcination temperature, the peak intensity ratio of the Pt (111) surface is too large. This is believed to be because when Pt is reduced and supported on a carbon carrier, the most stable Pt (111) surface grows preferentially, and in the case of no calcination or low calcination temperature, the Pt (111) surface is maintained. It is believed that when these electrode catalysts are calcined at an appropriate temperature, as the particle size of the catalyst metal particles increases, the (111) surface, (200) surface (equivalent to the (100) surface) and (220) surface (equivalent to the (110) surface) of Pt compete for growth.
[0180] At this time, if the oxygen partial pressure during calcination is less than 4.0 Pa, the peak intensity ratio of the Pt (111) plane exceeds 0.630, and the catalytic activity decreases (Comparative Examples 1 and 2). This is considered to be due to excessive growth of the Pt (111) plane under low oxygen partial pressure conditions.
[0181] On the other hand, if the oxygen partial pressure during calcination exceeds 800 Pa, the peak intensity ratio of the Pt(111) surface is less than 0.626, and the catalyst activity decreases (Comparative Examples 3 to 5). This is believed to be because if the oxygen partial pressure during calcination exceeds 800 Pa, high partial pressure oxygen is adsorbed on the Pt(111) surface, hindering the growth of the Pt(111) surface.
[0182] In addition, it was confirmed that the particle size of the catalyst metal particles increased rapidly when the electrode catalyst was calcined under the condition of oxygen partial pressure exceeding 1000 Pa (Comparative Examples 4 and 5). This is considered to be because the high partial pressure of oxygen caused the combustion of the carbon support, which promoted the sintering of the catalyst metal particles.
[0183] Table 2 demonstrates that the above tendency is exhibited even when the type of the carbon support is changed, and that the desired effect of the present invention is exhibited by the electrode catalyst specified in the present invention.
Claims
1. A fuel cell electrode catalyst, comprising a carbon carrier carrying catalyst metal particles consisting of Pt or a Pt alloy, When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (111) plane represented by the following formula is 0.626 to 0.630, Pt(111) peak intensity ratio = Pt(111) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity).
2. The fuel cell electrode catalyst according to claim 1, When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (200) plane represented by the following formula is 0.240 to 0.243, Pt(200) peak intensity ratio = Pt(200) peak intensity / (Pt(111) peak intensity + Pt(200) peak intensity + Pt(220) peak intensity).
3. The fuel cell electrode catalyst according to claim 1, When the electrode catalyst is subjected to XRD measurement, the peak intensity ratio of the Pt (220) plane represented by the following formula is 0.129 to 0.132, Pt (220) peak intensity ratio = Pt (220) peak intensity / (Pt (111) peak intensity + Pt (200) peak intensity + Pt (220) peak intensity).
4. The fuel cell electrode catalyst according to any one of claims 1 to 3, The particle diameter of the catalyst metal particles is 3.0 nm or more and 5.0 nm or less.
5. The fuel cell electrode catalyst according to any one of claims 1 to 3, The carbon support is particles of furnace conductive carbon black.
6. The fuel cell electrode catalyst according to any one of claims 1 to 3, The supported amount of the catalytic metal particles, represented by a ratio of the mass of the catalytic metal particles to the total mass of the electrode catalyst, is 1.0 mass % or more and 50 mass % or less. 7 . A cathode of a fuel cell, comprising a catalyst layer, wherein the catalyst layer comprises the fuel cell electrode catalyst according to claim 1 .
8. A fuel cell electrode assembly comprising the cathode according to claim 7. 9 . A fuel cell comprising the fuel cell electrode assembly according to claim 8 .
10. A method for producing a fuel cell electrode catalyst, comprising: contacting the carbon support with a catalyst metal precursor; reducing the catalyst metal precursor to support catalyst metal particles on the carbon support to obtain an electrode catalyst precursor; as well as The electrode catalyst precursor is calcined under the conditions of an oxygen partial pressure of 4.0 Pa to 800 Pa and a temperature of 500° C. to 1100° C.
11. The method for producing a fuel cell electrode catalyst according to claim 10, The calcination is performed under reduced pressure.
12. The method for producing a fuel cell electrode catalyst according to claim 10, The calcination is performed under the flow of an inert gas.
Citation Information
Patent Citations
Preparation of platinum-supported catalyst
JP1996084930A
Catalyst for air electrode of high polymer solid electrolyte type fuel cell and its manufacturing method
JP2003142112A